The importance of crowdfunding in small and medium-sized enterprises - Miranda, Inês Julião (2021)
The main goal of this study is to analyse the importance of crowdfunding in SMEs in Portugal, and thus an empirical research of the most recent bibliographic contributions on crowdfunding was carried out in order to characterize the phenomenon in Portugal, the identification and functioning of the active platforms, existing regulation, the success factors of the projects and some successful cases. It was also identified through the collected data the importance of SMEs in Portugal and the evolution of bank loans as well as the evolution of crowdfunding in Portugal. All empirical data throughout the study are, whenever possible, with reference to December 2019. The results of the research carried out show the importance that SMEs have in the Portuguese economy and how they are still very dependent on banks in obtaining a long-term loan, however, there is tendency to decrease over the years. Crowdfunding has been gaining more and more importance over the years both in Portugal and in the rest of the world and it has characterized itself as an asset in reducing bank dependence, making it an increasingly reliable alternative for SMEs in Portugal, being important to create an economy more connected with society.